Measuring the efficiency of Indian cement companies utilizing data envelopment analysis during the pre and post recession period - Banerjee, Arindam (Serbian Journal of Management, 2018)
The present research work was conducted to measure the efficiency of the cement companies in Indian Scenario by utilizing the concept of Data Envelopment Analysis during the pre and post period of recession during the recent global turmoil. In the present study two outputs (related to profit and sales) and three inputs related to cost are taken into consideration .Input oriented variable return to scale has been used for this paper. Linear program has been developed to measure the efficiency and super efficiency scores of the different cement companies. A further endeavour has been made in this paper to understand if recession really did have any impact on the cement industry by utilizing spearman rank correlation technique.